Nine Traditional Chinese Medicine Groups of Depression among Adolescents in Muang District, Nakhon Ratchasima Province - Danthaiwattana, Sayada; Solod, Wanchat (Journal of Health Sciences and Wellness, 2024)
The purpose of this descriptive research was to study the relationship between nine Chinese medicine syndromes and depression among adolescents in Muang district, Nakhon Ratchasima province. The research method used by the researcher was using a sample of 400 adolescents aged between 11 and 20 years from the area of Muang district, Nakhon Ratchasima province, with the following research tools: (1) personal factor questionnaire, (2) Thai version of the Patient Health Questionnaire for Adolescents (PHQ-A), and (3) checklist for the nine body conditions of traditional Chinese medicine. The results of data analysis showed that 289 out of 400 subjects had mild to severe depression, most of whom were females, with the age range between 16 and 20 years old. The results also found that the nine physical characteristics of Chinese medicine were positively correlated with adolescent depression at significant level of 0.01. It was found that the conditions group with the highest correlation was group 8, in which obstructive qi (breath) physical state was associated with depression of adolescents at the moderate association level (r=0.453). The results showed that obstructive qi (breath) conditions have the highest level of association with depression among adolescents, which was consistent with traditional Chinese medicine theory and related research. Therefore, depression should be prevented from the beginning, and it should be taken care of by balancing emotions, and eating food that has the property of diffusing Lung Qi and stimulating the flow of Qi, including doing body exercises.